UNSUR KEBARUAN DALAM DESAIN INDUSTRI KEMASAN MINUMAN JAHE - Allya Nadhira Putri; Simona Bustani (Reformasi Hukum Trisakti, 2022)
In accordance with Article 2 of the Industrial Design Law, PT Total Asri Sumber Alam and PT Aneka Boga Citra engaged in an industrial design dispute over the alleged lack of novelty in the packaging for ginger beverages held by PT Aneka Boga Citra. The main issue is how to evaluate the novelty of the ginger beverage packaging industry design in order to obtain industrial design rights based on the Industrial Design Law and what are the legal ramifications of the Supreme Court's decision to declare the dispute over the novelty of the ginger beverage packaging industrial design that belongs to PT Total Asri Sumber Alam with ginger beverage packaging industry design owned by PT Various Boga Citra. The research is normative legal research, descriptive in nature, using secondary data, described qualitatively and conclusions are also by deductive method. This results because of the industrial design of PT Aneka Boga Citra has a configuration of shapes, images and color composition that is similar to the industrial design previously published by PT Total Asri Sumber Alam, then the industrial design of PT Aneka Boga Citra is not a new industrial design in line with Article 2 of the Industrial Design Law.